21st-Century civil aviation: Is it on course or is it over-confident and complacent? – thoughts on the conundrum of aviation and the environment. (18th January 2017) - Poll, D.I.A.
ABSTRACT: Aviation brings great commercial and social benefits and, as the global economy develops, the demand for air transport is expected to grow. However, aviation also contributes to climate change and there is increasing international pressure to limit mean global temperature rise. Therefore, the future success of aviation is likely to depend upon the industry's ability to hold its environmental impact within politically acceptable limits. This paper describes aviation's interaction with climate and sets out, in broad terms, the challenge facing the industry. The prospects for mitigating the adverse effects by advanced technology working through aircraft design and manufacture are assessed and some potential restrictions imposed by airport infrastructure are identified. Some consideration is also given to the practicalities imposed by airline economics and the likely impact of the recent ICAO regulations, plus the proposed global-based market measures scheme for aviation carbon offset. It is argued that the environmental problem is not just about carbon dioxide emissions and that aircraft technology improvement alone is unlikely to provide a complete solution. The observation that, in current operations, the total fuel used is almost twice the minimum required suggests a need to recognise a broader ownership of the problem and broader responsibility for the solution. However, improvements in the overall system efficiency will probably need to be driven by additional regulation and the imposition of other financial measures. The overall conclusion is that the actions currently being taken and currently being proposed are probably not sufficient in themselves to meet the challenge of climate change. However, it appears that there is more that can be done and, provided that action is taken soon, there are some grounds for optimism that aviation will still be able to meet the needs of society in the 21 st century.